PENGGUNAAN METODE KUMON UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA MTS - Rifqi Hidayat; Desy Lusiyana; Susi Setiyawati (Integral : Pendidikan Matematika, 2017)
The research is based on the law of mathematics conceps understanding. The research is Quasi Experimental research. The research design is used Nonequivalent Control Group Design and sample collection . The population in the research is the students of class 7th MTs Yapik Sindangjawa Kabupaten Cirebon, academic year 201 5/2016. The technique in the research is Sampling Purposive. The sample of the research is the 7th qraders 31 th student class 7th A is classes eksperimental and 29 th student class 7th B is classes control. Based on the result of the difference of the average of post-test using the test of Independent Sample T-Test equals sig (1 tailed) score 0,001 < 0,05 means H0 ejected show the mathematics concepts understanding skill which is using kumon method is better than the students who are learning by conventional learning process. And then the difference of the average using of N-gain using the test of Independent Sample t-test equals sig score (1 tiled) 0,0005 < 0,05 means H0 ejected show the improvement of mathematics concept understanding skill which is using kumon method is better than the students who are learning by conventional learning process.